The effect of exercise on IL-6-induced cachexia in the Apc(Min/+) mouse - Puppa, Melissa J. (Springer-Verlag, 2011)
BACKGROUND: Cachexia involves unintentional body weight loss including diminished muscle and adipose tissue mass and is associated with an underlying disease. Systemic overexpression of IL-6 accelerates cachexia in the Apc(Min/+) mouse, but does not induce wasting in control C57BL/6 mice. With many chronic diseases, chronic inflammation and metabolic dysfunction can be improved with moderate exercise. A direct effect of regular moderate exercise on the prevention of IL-6-induced cachexia in the Apc(Min/+) mouse has not been investigated. The purpose of this study was to assess the effects of exercise on the development of cachexia in the Apc(Min/+) mouse. METHODS: Mice were randomly assigned to moderate treadmill exercise (18 m/min, 1 h, 6 days/week, 5% grade) or cage control (CC) groups from 6 to 14 weeks of age. At 12 weeks of age, mice were electroporated with either IL-6-containing or control plasmid into the quadriceps muscle. Mice were killed after 2 weeks of systemic IL-6 overexpression or control treatment. RESULTS: IL-6 overexpression induced an 8% loss in body weight in CC mice, which was significantly attenuated by exercise. IL-6 overexpression in CC mice increased fasting insulin and triglyceride levels, which were normalized by exercise, and associated with increased oxidative capacity, an induction of AKT signaling, and a repression of AMPK signaling in muscle. These exercise-induced changes occurred despite elevated inflammatory signaling in skeletal muscle. CONCLUSION: We conclude that moderate-intensity exercise can attenuate IL-6-dependent cachexia in Apc(Min/+) mice, independent of changes in IL-6 concentration and muscle inflammatory signaling. The exercise effect was associated with improved insulin sensitivity and improved energy status in the muscle.